Exu Feminino e o matriarcado nagô: indagações sobre o princípio feminino de Exu na tradição dos candomblés yorubá-nagô e a emancipação das “Exu de Saia” - Alexandre, Claudia Regina (2021)
The present study approaches aspects that refer to the female principle in Exu and the Nagô Candomblés, with the intention of understanding the absence or silencing of female cults of the messenger orixá as part of the hierarchy that originated this belief system. This search includes questions about the relationships established between the women of terreiros, male “domination” and female “emancipation” in traditions of Yoruba origin, heritage of the peoples of West Africa, which include the Nagô complex that was organized since from the 19th century, in Bahia, its origins in Brazil going back to the regions that correspond, today, to the Southwest and Center of Nigeria and to the South and Center of the Republic of Benin (formerly Dahomey). This research is inserted in the field of Science of Religion, in dialogue with decolonial theories, with an interest in symbolic languages and representations, above all, of the Female Exu cults in the field of Afro-Brazilian religions and the possible relationships with the construction of this history, observing confrontations of intersectional oppressions and structural power domination (Crenshaw, 2018; Collins, 2019; Davis, 1981), which mark an important period in the history and participation of black women in the formation of Brazilian society, which has not yet deserved specific studies